Negotiation - Brett, Jeanne; Thompson, Leigh (Organizational behavior and human decision processes, 2016)
•Reviews behavioral negotiation theory and research.•Focuses on empirical studies of two-party negotiations.•Examines factors affecting negotiators’ interests and priorities, strategies and social interactions, and outcomes.•Reviews psychological factors: cognitions, biases, personality, motivation, emotions and trust.•Reviews social-environmental factors: reputation, relationship, gender, BATNA, status, and culture.•Discusses future directions for negotiation research. Negotiation has been an important area of research within organizational behavior and management science for the past 50years. In this review, we adapt Brett’s model of culture and negotiation (Brett, 2000) and use it as an organizing guide to examine the factors that research has shown to affect 3 key measures, namely: negotiators’ interests and priorities, strategies and social interactions, and outcomes. Specifically, the model focuses on psychological factors including cognitions and biases, personality, motivation, emotions and inclination to trust; and social-environmental factors including reputation and relationship, gender, power and status, and culture. We conclude with a discussion of how future directions might address some of the limitations of current research.